(untitled) (Scientific journal of the Fergana State University, 2024)
This article outlines some considerations concerning the harmonious development of the physical and mental resources of young people, especially the wide use of the possibilities of physical culture and sport, defined as one of the main directions of state policy, that physical culture and sport play an important role in achieving by students not only physical but also spiritual perfection.